The Correlation Between Reading Speed and Vocabulary Mastery in Second Grade of SMK N 1 Kinali in The Academic Year 2021/2022 - Herlina, Herlina; Melani, Melyann (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research was to find out whether there was any significant correlation between students’ Reading Speed and Students’ Vocabulary Mastery in Second Grade of SMK N 1 Kinali in the Academic Year 2021/2022. The design of this research was correlational research. The instruments of this research were reading speed tests for measuring students’ reading speed and vocabulary mastery tests for measuring students’ vocabulary mastery. The population of this research is all of the second grade of SMK N 1 Kinali in the academic year of 2021/2022 which consists of 4 classes. The results of the research showed that there was a correlation between students’ Reading Speed and Students' Vocabulary Mastery in the Second Grade of SMK N 1 Kinali in the Academic Year 2021/2022. The researcher found that the coefficient of correlation between students’ Reading Speed and Students’ Vocabulary Mastery is 0,371. It showed that there was a low correlation between students’ reading speed and vocabulary mastery, it included the scale of r interpretation scores between 0,20-0,49. Furthermore, with df =31. And the level of significance 0,05 (α= 5%) obtained 0,355. So, rxy = 0,371 > t table 0,355. So, Ha is accepted and Ho was rejected. It means that there was a low correlation between students’ Reading Speed and Students’ Vocabulary Mastery.